Assessing indoor gas phase oxidation capacity through real-time measurements of HONO and NOx in Guangzhou, China. Issue 8 (19th July 2019) - Liu, Jiangping; Li, Sheng; Zeng, Jiafa; Mekic, Majda; Yu, Zhujun; Zhou, Wentao; Loisel, Gwendal; Gandolfo, Adrien; Song, Wei; Wang, Xinming; Zhou, Zhen; Herrmann, Hartmut; et al.
Abstract : The photolysis of nitrous acid (HONO) is the main initiation source of hydroxyl radical (OH) which in turn is the main oxidant controlling the oxidation capacity of the indoor atmosphere. Abstract : The hydroxyl radical (OH) is one of the most important oxidants controlling the oxidation capacity of the indoor atmosphere. One of the main OH sources indoors is the photolysis of nitrous acid (HONO). In this study, real-time measurements of HONO, nitrogen oxides (NO x ) and ozone (O3 ) in an indoor environment in Guangzhou, China, were performed under two different conditions: (1) in the absence of any human activity and (2) in the presence of cooking. The maximum NO x and HONO levels drastically increased from 15 and 4 ppb in the absence of human activity to 135 and 40 ppb during the cooking event, respectively. The photon flux was determined for the sunlit room, which has a closed south-east oriented window. The photon flux was used to estimate the photolysis rate constants of NO2, J (NO2 ), and HONO, J (HONO), which span the range between 8 × 10 −5 and 1.5 × 10 −5 s −1 in the morning from 9:30 to 11:45, and 8.5 × 10 −4 and 1.5 × 10 −4 s −1 at noon, respectively. The OH concentrations calculated by photostationary state (PSS) approach, observed around noon, are very similar, i.e., 2.4 × 10 6 and 3.1 × 10 6 cm −3 in the absence of human activity and during cooking, respectively. These results suggest that under "high NO x " conditions (NO x higher than a few ppb) and with direct sunlight in the room, the NO x and HONO chemistry would be similar, independent of the geographic location of the indoor environment, which facilitates future modeling studies focused on indoor gas phase oxidation capacity.